1
$\begingroup$

enter image description here

I am having a bit of trouble understanding the pasted excerpt. I think I might be missing something basic. As I understand it, the contrapositive of a conditional statement is where we take a conditional statement and both 1) flip the hypothesis and conclusion and 2) negate the q and p so we have ¬q -> ¬p

Looking at the truth table of the original p -> q I can convert each possibility to the contrapositive ¬q -> ¬p . So, for example, when p is True and q is False, the p -> q is false. I can now turn this case into the contrapositive by taking the q and negating it which is True and then take the p and negating it which is False.

What does this mean though that the contrapositive has the same truth value as p -> q? Like, the truth of table of p -> q was just a fact that was given to me. How do I know what the truth value for each possibility of ¬q -> ¬p is though? Is it simply that we can always convert the contrapositive back to the p -> q statement by "un-negating" the q and p in ¬q -> ¬p and then know the truth value based on original truth table for p -> q where we know it's only False when p is True and q is False?

Just generally confused. I hope my rambling question makes some sense.

Thanks in advance.

$\endgroup$
2
  • 1
    $\begingroup$ You can also ask yourself what would happen if not-q implied p instead, for then p implies q, which would lead to a contradiction. $\endgroup$ May 31 at 19:48
  • 2
    $\begingroup$ Set up a truth table, with the 4 possibilities of ($p$ true or false) and ($q$ true or false). In the table, for each of the 4 possibilities, evaluate the two statements that are allegedly equivalent. The statements will be equivalent if and only if they evaluate the same in each of the 4 rows of the truth table. $\endgroup$ May 31 at 19:49
2
$\begingroup$

Well, you can easily verify that the two statements are equivalent using a truth table, as you have done.

You might also use the definition $$p\rightarrow q \equiv \sim p \cup q$$ to show that both are equivalent.

If you want to gain some intuitive sense, $p\rightarrow q$ means "if $p$, then $q$". This means that the truth of $p$ indicates the truth of $q$. Whereas the second statement means "if not $q$, then not $p$". The two are clearly equivalent. To see this take, as an example, $p\equiv$ "it is cloudy" and $q\equiv$ "it is raining".

$\endgroup$
1
  • $\begingroup$ Thank you, that example does help! $\endgroup$
    – LuxuryMode
    Jun 1 at 0:29
1
$\begingroup$

I think something fundamental may be slipping past you. As I think you understand, the implication $p \Rightarrow q$ means that either the premise (which we're calling $p$) is false or the consequence (what we're calling $q$) is true (or possibly both).

But with this understanding, the truth values of the contrapositive are not arbitrary. Let's look at the contrapositive $\lnot q \Rightarrow \lnot p$. By our definition of an implication, this means the premise (whatever it may be) is false or the consequence (whatever it may be) is true. In this case, the premise is $\lnot q$, and that's false exactly when $q$ is true. Similarly, the consequence of the contrapositive is $\lnot p$, and that's true exactly when $p$ itself is false.

That means that $\lnot (\lnot q) \lor \lnot p$ (which is equivalent to the contrapositive) is true exactly when $\lnot p \lor q$ is true, so the contrapositive is true exactly when the original implication is true.

$\endgroup$
5
  • 1
    $\begingroup$ Thank you very much, I think this explained it. I think what I was missing was the actual "meaning" of an implication. I was looking at it as simply a table of rules where we know the only false case is when p is true and q is false. But there's a logic or sense to this in that when we have a premise and consequence, it can be true either because the premise is false or the conclusion is true. $\endgroup$
    – LuxuryMode
    Jun 1 at 0:14
  • 1
    $\begingroup$ Hence the only case where the implication is false is when p is true and q is false. With this, we can then think of the contrapositive $\lnot q \Rightarrow \lnot p$ and apply the same idea. We have a premise, in this case $\lnot q$, and a consequence $\lnot p$. In this case, for the premise to be false, q must be true. For the consequence to be true, p must be false. $\endgroup$
    – LuxuryMode
    Jun 1 at 0:14
  • 1
    $\begingroup$ This leaves us with the only case where the implication is false is when q is false (since in the case of the contraposition our premise is $\lnot q$ which evaluates to true) and when p is true which evaluates to false. $\endgroup$
    – LuxuryMode
    Jun 1 at 0:15
  • 1
    $\begingroup$ So what we're doing in effect is saying if we took the truth table of if p then q and swapped the premise and consequence and also negated q and p, we will end up with the exact same truth values as the implication if p then q, namely that it is only false when q is false (making not q true) and when p is true (making not p false) which results in an implication where the hypothesis is true and the consequence is false which we know is false. Do I have this correctly understood now? $\endgroup$
    – LuxuryMode
    Jun 1 at 0:15
  • 1
    $\begingroup$ That's exactly right. I'm glad I could help. $\endgroup$ Jun 1 at 0:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.